PELAYANAN PEMBUATAN PASPOR PADA KANTOR IMIGRASI KELAS II KOTA DUMAI - Cahya Tri Wulandari; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Service is one that should get the attention of the government, until now, public complaints in the service that is still felt the news in various mass media. The aim of this study is (1) to find out the passport service and; (2) to find out what factors that influence the Passport Service. The theory used in this research is Widodo (2001:270-271) : (1) Service Procedures, (2) Completion Time, (3) Service Charge, (4) Service Product, (5) Facilities and Infrastructure, (6) Officer Competencies. This research methodology used is qualitative descriptive approach. Sources of this research are 3 (three) head divisions, 1 (one) office staff, and 5 (five) society. The technique of data collection in this research are interview, observation, and documentation. The result of this research shows that the Passport Service at Immigration Office Class II Dumai is not maximal yet, because there are some indicators such as facilities and infrastructures and competence of officers which considered not satisfying yet for society. While other indicators such as service procedures, completion time, service cost, and service product is already well. Factors that affect the services at the Immigration Office Class II Dumai are a network system problem and the response of officers who are still not good.Keywords: Public Service, Passport